2021
DOI: 10.33472/afjbs.3.1.2021.58-66
|View full text |Cite
|
Sign up to set email alerts
|

Removal of nitrogen and phosphorus from agro-industrial wastewater by using microalgae collected from coastal region of peninsular Malaysia

Abstract: The potential of microalgae as a source of renewable energy based on wastewater has received increasing interest worldwide in recent decades. A freshwater microalga Chlorella vulgaris was investigated for its ability to remove both nitrogen and phosphorus from three industrial wastewaters which were diluted in microalgae in two different proportions (namely, 50% and 75%). C. vulgaris grew fastest under 75% palm oil mill, and showed an maximum cell density (0.408 ± 0.012 g/L) for Palm Oil Mill Effluent (POME) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The decrease in conductivity results in the decrease in conductivity in nutrient solution 57 . Bhuyar et al also reported that, as Chlorella utilized the dissolved solids, the TDS and salinity decreased 58 . Since the dissolved solids also plays a role in the salinity of the medium, salinity decreased at the same time with TDS.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The decrease in conductivity results in the decrease in conductivity in nutrient solution 57 . Bhuyar et al also reported that, as Chlorella utilized the dissolved solids, the TDS and salinity decreased 58 . Since the dissolved solids also plays a role in the salinity of the medium, salinity decreased at the same time with TDS.…”
Section: Resultsmentioning
confidence: 95%
“…57 Bhuyar et al also reported that, as Chlorella utilized the dissolved solids, the TDS and salinity decreased. 58 Since the dissolved solids also plays a role in the salinity of the medium, salinity decreased at the same time with TDS. In the Figure 2f, the relation between dissolved oxygen and microalgal growth has presented.…”
Section: Relation Between Microalgal Growth and Other Chemical Stimul...mentioning
confidence: 99%
“…Referring to Figures 2c and 3c, the ammonia removal was better for the POME treated with Chlorella pyrenoidosa (single group) and Chlorella vulgaris + Chlorella pyrenoidosa (combine group) due to the lower removal ratio of ammonia removal by Chlorella vulgaris (Bhuyar et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…C. vulgaris has also been demonstrated to adapt to highly concentrated municipal wastewater streams generated by the dewatering of sludge from primary- and secondary-settling (centrate), as proposed by Zhou et al [ 7 ]. Besides municipal, urban or domestic wastewaters, several studies have shown the great bioremediation potential of this microalga on nutrients’ removal from hydroponic greenhouse cultivation wastewaters, piggery wastewaters, textile wastewaters, paper industry effluents, palm oil mill effluents, riboflavin manufacturing wastewaters, and fertiliser industrial wastewaters, among others [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%